(3GJaGbjI ZRI(B- (3CQjMG ChdG (B:s (3GdMd GdeQahV (B/s - (3GdMhJ, Tajbs ((3HjQhJ (B:s (3OGQ GdESJbdGd ddOQGSGJ h GdfTQ ,s, 1994)
(3JYhO (B((3OGQ GdGSJbdGd(B) (3Gdi GUOGQ gPg GdSdSdI h djS gfGc ef ehVhY GcKQ GgejI ef efGbTI GJaGbjI (B((3ZRI (B- (3GQjMG GhdG(B) (3h dYd GdaGQb GdcHjQ Hjf GdGeS h Gdjhe aj eSjQI GdfVGd ddTYH GdadSWjfj jXgQ ef NdGd GdebGQfI Hjf ehVhYj GdhQbJjf GdGhdi h GdKGfjI ef gPg GdSdSdI aGdhQbI GdGhdi JfGhdJ SjQI GdTjN GdeLGgO YR GdOjf GdbSGe aj JGQjN adSWjf h GeG gPg GdhQbI GdKGfjI aJMdd GJaGbjI GHQR eG ajgG jJfGbV cd GdJfGbV eY SjQI Pdc GdTjN GdeLGgOs
Keywords: (3GJaGbjIZRIs; (3adSWjfs